PENGARUH CARA PEMOTONGAN DAN PEMBERIAN ZPT AUKSIN DENGAN KONSENTRASI BERBEDA TERHADAP PERTUMBUHAN SETEK PUCUK JAMBU AIR (Syzygium aqueum L.) PADA MEDIA OASIS - Suci Yulianti, Tri; Rahmadina; Khairunnisa (Universitas Cokroaminoto Palopo, 2025)
Water apple contains high levels of nutrition and vitamin C for the body. This provides great potential for water apple because the demand for production increases every year. The decline in water apple production in North Sumatra is caused by poor seed types. Vegetative propagation by cuttings, cutting methods and administration of auxin PGR are expected to produce quality seeds. This study aims to determine the effect of cutting methods, administration of auxin PGR, and the interaction of cutting methods and auxin PGR on the growth of water apple shoot cuttings (Syzygium aqueum L.) on oasis media. This study used a factorial randomized block design (RAK) with 2 factors and 3 replications. The data obtained were analyzed using the ANOVA test and continued with the Duncan Multiple Range Test (DMRT). The results showed that the best cutting method treatment was flat cutting on the percentage of cutting survival and net assimilation rate. The best administration of auxin PGR was a concentration of 100 ppm on the percentage of cutting survival, early emergence of shoots, number of shoots, relative growth rate and net assimilation rate and a concentration of 200 ppm on root length and number of roots.